AN ANALYSIS OF SLANG LANGUAGE AS SOCIAL VARIATION PRODUCED BY MEN AND WOMEN’S SPEECH IN LAMONGAN - Moh Nurman (Universitas Islam Lamongan, 2018)
This research aims to describe the Slang Language as a social variation produced by men and women’s speech in the age of 18-25 years old found in Lamongan. The research used ethnography research design. The subjects were three men and three women from Lamongan. to collect the data, this present study used interview and observation. The data obtained, then, were analyzed qualitatively by describing the language variation used by the men and the women’s speech in Lamongan. The result shows that language variation was used by those three men and three women. Mostly, they used language in various style when they communicated to their friends. It often took place when they gather among their friends. Specific language became pride a the level of their social. Some factors that caused the men and women’s speech used the language variation dealt with the environment, association, media, social status and different culture